Machinery for mechanical engineers - Baharom, M.B. (2019)
Rotating machinery turnaround is very crucial to manufacturing plants to ensure that equipment is being serviced prior to being used in a long continuous service operation. This chapter discusses on the preparation, execution, and post-turnaround activities of rotating machineries. The contents of knowledge in this chapter are suitable for turnaround planners, mechanical engineers, and contractors. Examples of good practices in turnaround activities and samples of work execution methods are presented in this chapter. Â© The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2019.